Primerjava sočasnih meritev elektrokemijskega šuma in mehanskih parametrov med procesi napetostno-korozijskega pokanja - Bajt Leban, Mirjam (Materiali in tehnologije, 2000)
The main aim of the research work was to asses basic characteristics of electrochemical noise generated by stress-corrosion cracking, and especially to find a correlation between the electrochemical and mehanical quantities. Electrochemical noise was measured during slow constant increasing of stress (modified Slow Strain Rate Test) on tensile tube made from austenitic stainless steel of the type AISI 304, in sensitized and nonsensitized condition. One of the objectives of this research was to investigate the possibility of electrochemical noise method for studying stress-corrosion processes. After the reaching yielding point, voltage and current spikes, as well as elongation transients, all appearing at the same time, were detected. Afterwards, the cracking velocities were determined from the time series of elongation, and compared to characteristic parameters of the measured electrochemical noise. The results of the comparision indicated that the amplitudes of the electrochemical noise spikes are lineary dependent upon cracking velocity. It has to be pointed out, that the knowledge of elecrochemical conditions and mechanical changes generated by cracking processes by themselves, cannot form revalant information concering the cracking mechanisms. In order to get better overview to this problem additional fractographic inspections of cracking surfaces has to be performed.
Keywords: metalografske preiskave; elektrokemijski šum; pokanje; korozija; vodikova krhkost; interkristalna korozija